2021
DOI: 10.3390/rs13081468
|View full text |Cite
|
Sign up to set email alerts
|

Urban Thermal Characteristics of Local Climate Zones and Their Mitigation Measures across Cities in Different Climate Zones of China

Abstract: Understanding the urban thermal environment is vital for improving urban planning and strategy development when mitigating urban heat islands. However, urban thermal characteristics of local climate zones (LCZ) are different within cities and most studies lack regional perspective. This study explored surface thermal performances of cities in three urban agglomerations (Jing-Jin-Ji, Yangtze River Delta and Pearl River Delta) in China using MODIS land surface temperature (LST). Besides that, the diurnal and sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 33 publications
(54 reference statements)
2
20
0
Order By: Relevance
“…In the case investigated in this study (Babolsar and Fereydonkenar), tourism had a significant moderating effect on the LST in the tourism zones through developing green spaces that were constantly irrigated, and constructing on bare lands that were generally covered with sand. Although this study focused on the effects of the physical development of tourism instead of urban development, its results on the correlation between the land cover indices such as NDVI, MNDWI and EBBI with the LST are consistent with previous research [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the case investigated in this study (Babolsar and Fereydonkenar), tourism had a significant moderating effect on the LST in the tourism zones through developing green spaces that were constantly irrigated, and constructing on bare lands that were generally covered with sand. Although this study focused on the effects of the physical development of tourism instead of urban development, its results on the correlation between the land cover indices such as NDVI, MNDWI and EBBI with the LST are consistent with previous research [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Discussionsupporting
confidence: 89%
“…This result shows that the LST has increased with increases in the area of built-up and bare lands, while increasing the area of vegetation and water bodies has reduced the LST in the study area. These particular results is in line with previous research showing the significant effect of vegetation on the LST [37,[100][101][102][103][104][105][106][107][108][109][110]. In this regard, Rahman et al [97], by modeling the spatial changes in the coastal lands and their effects on the LST characteristics, showed that physical changes due to urban development and built-up lands have a direct and significant effect on the LST, and this could pose a challenge for the residents of the studied areas in the future.…”
Section: Discussionsupporting
confidence: 88%
“…In summer and fall seasons, the lowest mean LSTs were over both classes (Figure 8), more notably in summer. During warm seasons, evapotranspiration is high (higher sun elevation angle), and most of the heat is transported as latent heat [47]. Accordingly, low mean LSTs in winter were not found across LCZs B and D (Figure 8), and both showed positive LST departure values (Figure 6) as evapotranspiration is lower in this season.…”
Section: Discussionmentioning
confidence: 98%
“…Developing cities on natural lands causes the expansion and replacement of impervious urban surfaces that retain less moisture compared to the natural coverages. Hence, the significant differences in heat capacity, roughness, and Albedo collectively make the urban lands warmer than their surrounding rural environments [ 14 , 25 , 26 , 27 , 28 , 29 ]. The effects of UHI can be intensified by heat emitted from transportation, heating systems in homes, service centers, and industrial environments, as well as indoor ventilation systems [ 19 ].…”
Section: Introductionmentioning
confidence: 99%